Differences in wage growth by education level: do less-educated workers gain less from work experience? - Helen Connolly; Peter Gottschalk (Institute for the Study of Labor (IZA), 2006)
This paper revisits the old question of whether wage growth differs by education level. Do more educated workers invest more than less educated workers in firm specific, sector specific or general human capital? Do they gain more from improved job match? The paper makes both a methodological and a substantive contribution by offering an alternative strategy for separately identifying returns to general experience, sector specific experience, firm tenure, and job match. Our empirical results, based on the Survey of Income and Program Participation, show that overall wage growth is higher for more-educated workers. This reflects higher returns to general experience for college graduates and higher returns to sector experience for high school graduates. Improvements in job match grow monotonically with education.
urn:nbn:de:101:1-20090825291
Keywords: 330